Impacts of microwatershed pollution in Huanuco on the quality of life of people - Bustamante-Paulino, Nicéforo (2022)
Huanuco is located in the center of Peru. In its surroundings it is bathed by three basins such as the Marañón, Huallaga and Pachitea, which in turn receive the tribute of their waters from a set of micro-basins, such as the Nupe, Murmunya, Lauricocha, Carhuacocha, Vizcarra, Higueras, Huacar, the Eco , Llata, Quera, among others. The purpose of the research was to detect the factors of the contamination process of the basins and micro-basins of Huánuco, to test the inventory of the main micro-basins of Huánuco in the quality of life of its inhabitants and to determine the role of environmental education in the preservation of basins and micro-basins. The main method was observation, on-site view of the problem, information gathering, consultation of bibliographic sources and their analysis. The result was a high degree of contamination of the micro-watersheds, little preservation policy and poor ecological and environmental education on the part of the inhabitants that negatively affects the quality of life of the Huanuco population.